Struktur dan Konstruksi sebagai Agen Transformasi dalam Desain Arsitektur Nusantara - Nurfahmi Muchlis; Hari Purnomo; Irvansyah Irvansyah (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2019)
The transformation of Nusantara architectures is more discussed in the variety of visual languages. The structure and construction of Nusantara architectures become an agent to form recent variants while sustaining the visual style identities. So the forces and loads resemble architectural appearance. The structure and construction that had changed, indicating the sustained development of Nusantara architectures. The houses in the South Sulawesi have presented this for instance. This study aims to examine the structural capabilities and construction of Nusantara architectures transformed into developing variants. Descriptive methods are implemented to discuss Bugis houses in Makassar and Bulukumba, and Selayar house in Selayar Island. The results present that the variants of the Nusantara architectures are formed because of the application of a structural system that does not change. It adapts to the context of the site contours and the selection of construction wood materials available on site.